Eu3+ ions doped zinc borotellurite glass system for white light laser application: structural, physical, optical properties, and Judd-Ofelt theory - Adamu, S. B.; M. K., Halimah; Chan, K. T.; Muhammad, F. D.; Nazrin, S. N.; Tafida, R. A. (Elsevier, 2022)
The melt-quenching method was used to fabricate zinc borotellurite glasses of composition [{(TeO2)0.7 (B2O3)0.3}0.7 (ZnO)0.3](1-y) (Eu2O3)y, with 0.01 = y ≤ 0.05 M fraction. The calculated density and molar volume values lies between 4.74 and 5.15 g/cm3, and 24.58 and 25.61 cm3/mol. The optical properties were analysed and discussed. The estimated optical band gap (direct and indirect) energies decrease from 3.49 to 3.05 eV and 3.11 to 2.81 eV, whereas the Urbach energy and reflective index increase from 0.262 to 0.334 eV and 2.368 to 2.450 with Eu2O3 content. The evaluated Racah parameters (B and C) ranges from 92.60 to 119.86 cm−1 and from 626.64 to 643.35cm−1, respectively. The calculated Judd-Ofelt Ω2 parameter increases from (2.78 to 3.93)×10−20cm2. Furthermore, the gain bandwidth and optical gain value were found between (14.295 to20.340)×10−28cm2 and (12.576 to 15.693)×10−25cm2, respectively, for the 5D2 → 7F2 transition. In addition, stimulated emission cross-section and branching ratio values of 14.029×10−22cm2 and 66.54% were achieved from TBZEu0.04 prepared glass, indicating a promising potential for white-light lasing application.